The fables of Jesus in the gospel of Luke a new foundation for the study of parables - Strong, Justin David; Verlag Ferdinand Schöningh (Paderborn Brill | Schöningh, 2021)
The Fables of Jesus in the Gospel of Luke introduces the world of the ancient fable to biblical scholarship and argues that Jesus’s parables in Luke’s gospel belong to the ancient fable tradition.Jesus is regarded as the first figure in history to use the parable genre with any regularity—a remarkable historical curiosity that serves as the foundation for many assumptions in New Testament scholarship. The Fables of Jesus in the Gospel of Luke challenges this consensus, situating the parables within a literary context unknown to biblical scholarship: the ancient fable. After introducing the ancient fable, the “parables” of Jesus in Luke’s gospel are used as a testing ground to demon - strate that they are identical to first-century fables. This challenges many conven - tional assumptions about parables, Luke’s gospel, and the relationship of Jesus to the storytelling traditions of the Mediterranean world. This study offers multitudes of new parallels to the otherwise enigmatic parable tradition, opens an exciting new venue for comparative exploration, and lays a new foundation upon which to study the fables of Jesus.
Online resource; title from title screen (viewed October 28, 2021)
Keywords: Jesus Christ -- Parables; Jésus-Christ - Paraboles; Jesus Christ; Bible -- Criticism, Narrative; Bible -- Criticism, interpretation, etc; Bible; Parables, Biblical; Criticism, interpretation, etc; Aesop; New Teastament; Biblical Studies; Classical Studies; Judaism; Gospel Interpretation; Neues Testament; Biblische Studien; Klassizistik; Judentum; Erstes Jahrhundert; Hochschulschrift